MOLD STRAINS ISOLATED FROM UNFINISHED AND FINISHED LEATHER GOODS AND SHOES - (:unkn) unknown (AMER LEATHER CHEMISTS ASSN, 1994)
A series of Turkish leather samples ranging from freshly prepared chrome tanned blue crust to new and used shoes was examined for fungal contamination. Sixty two species of fungi from 23 genera were isolated and identified. These included Absidia, Acremonium, Aspergillus, Basipetospora, Byssochlamys, Chrysonilia, Cladosporium, Emericella, Eupenicillium, Eurotium, Fusarium, Monascus, Moniliella, Mucor, Neosartorya, Paecilomyces, Penicillium, Phialophora, Scopuloriopsis, Stachybotrys, Trichoderma, Trichosporon, and Verticillium. Eighteen of these species were found to be mycotic agents capable of causing primary skin infection. Aspergilli and Penicillia species were found on chrome tanned leathers and shoes. The number of mold species isolated increased with time of storage particularly under humid conditions. Fifty three percent of the species found on stored unused shoes were also isolated from used shoes. This suggests that some mycotic infections could be due to the contamination of finished leather during storage or from the shoes contaminated during the shoe making process.